Manajemen Pembiayaan Pendidikan untuk Peningkatan Kualitas Sumber Daya Manusia di Madrasah Aliyah Negeri - Inggrid Prolina, Nina; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
Education is the key to human resource development, and adequate funding is a crucial factor in achieving quality education. This study explores various financing strategies implemented by MAN 2 Kota Bandung in improving the quality of its human resources. Through data analysis and literature review, this article aims to identify various sources of funding, such as budget allocation, government grants, community contributions, and partnerships with the private sector. The method used in this research is a qualitative case study method. The results of this study show that effective financial management has made a positive contribution to the enhancement and nurturing of human resources at MAN 2 Kota Bandung. This success is reflected in students' academic achievements, adequate educational facilities, and the improvement in the quality of educators. This article provides guidance for similar educational institutions in their efforts to enhance human resource quality through effective financial management.